Empowering Wetland Rice Farmers Through Strengthening Social Capital in Tomohon City - Charles R. Ngangi; Rine Kaunang; Stephano C. W. Ngangi; Caroline Betsy Diana Pakasi; Mukhlis Mukhlis (Postgraduate, University of Mataram, 2025)
The role of government and related institutions in farmers' social capital through networks, norms, and trust, can affect farmers. One form of influence is to increase the empowerment of farming communities through empowerment programs carried out by extension to farmers. The purpose of this research is to formulate a model of strengthening social capital in empowering farmers in farmer groups. This research was designed descriptively using interview and survey methods. The sampling method is purposive sampling (Purposive Sampling Method). The research respondents were farmers in Tara-tara Village and Kayawu Village with a total of 100 respondents. Data collection methods were carried out by interviewing and surveying respondents. Primary data were obtained from respondent farmers through direct interviews, secondary data were obtained from various related agencies. The research data obtained were analyzed through three processes, namely reducing data, presenting data, and verifying data. Data verification was done by triangulating primary data sources, namely in-depth interviews, observation, and documentation with secondary data. Data reduction was done by writing a summary of interviews with respondents while in the field. Meanwhile, data presentation was done by tabulation to classify the data. Data verification is done by drawing conclusions. The results show that social capital involves three main aspects. These include trust, norms, and networks. Each aspect is assessed based on the indicators that make it up which are then used to measure the average strength of social capital of farmers in Tomohon City